Aspects of climate variability during winter and summer in Central America - Maldonado Mora, Tito José (2015)
Climate variability during winter and summer in Central America is examined. In winter, we focused on the interaction between El Niño Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), the Caribbean low-level jet (CLLJ) and precipitation. Using the composite technique it is found that ENSO events are connected to CLLJ anomalies by modulating the sea-level pressure (SLP) near the east coast of the United States and the Aleutian Low. The pattern displayed by the SLP anomalies (SLPa) is also associated with the Pacific/North America pattern (PNA). During warm (cold) ENSO phases, negative (positive) anomalies in the SLP field over the east coast of North America produce cyclonic (anticyclonic) circulations at low levels. However, the ENSO signal in the SLPa and the PNA pattern are modulated by the phases of the PDO. Results indicate that when the ENSO and PDO are in phase (out of phase), the SLPa signal is enhanced (weakened or cancelled), affecting the CLLJ anomalies in both direction and intensity, also changing the spatial distribution of precipitation. During summer, the midsummer drought (MSD) in Central America is characterised in order to create annual indexes representing the timing of its phases (start, minimum and end), and other features relevant for MSD forecasting such as the intensity and the magnitude. The MSD intensity is defined as the minimum rainfall detected during the MSD, meanwhile the magnitude is the total precipitation divided by the total days between the start and end of the MSD. It is shown that the MSD extends along the Pacific coast, however, a similar MSD structure was detected also in two stations in the Caribbean side of Central America, located in Nicaragua. The MSD intensity and magnitude show a negative relationship with El Niño 3.4 and a positive relationship with the CLLJ index. However for the Caribbean stations the results were not statistically significant, which indicates that other processes might be modulating the precipitation during the MSD over the Caribbean coast. On the other hand, the temporal variables (start, minimum and end) show low and no significant correlations with the same indexes. The results from canonical correlation analysis (CCA) show good performance to study the MSD intensity and magnitude, however, for the temporal indexes the performance is not satisfactory due to the low skill to predict the MSD phases. Moreover, we find that CCA allows producing forecasts of the MSD intensity and magnitude using sea surface temperatures (SST) with leading times of up to 3 months. Using CCA as diagnostic tool it is found that during June, an SST dipole pattern upon the neighbouring waters to Central America is the main variability mode controlling the inter-annual variability of the MSD features. However, there is also evidence that the regional waters are playing an important role in the annual modulation of the MSD features. The waters in the PDO vicinity might be also controlling the rainfall during the MSD, however, exerting an opposite effect at the north and south regions of Central America.